Successful management of femoral trauma in a through-knee amputee with a previous malunited fracture: Implications and functional outcome. (October 2017) - Lineham, Beth; Harwood, Paul; Giannoudis, Peter
Background: After amputation patients are more likely to injure their residual limb. An injury of a previously amputated limb, especially if the residuum is not anatomically normal, poses a dilemma for management. Case Description and Methods: This case report discusses a femoral fracture sustained proximal to a through-knee amputation. Findings and outcomes: The fracture was at the site of a malunited fracture. A shortening osteotomy with bone graft was undertaken to improve alignment and prosthetic fit and remove poor-quality bone. This was stabilised using an intramedullary nail, supplemented with an anti-rotation plate. This fracture went on to uneventful union, and the patient was able to comfortably use a prosthesis with increased functionality compared with prior to the recent injury. Discussion: This management enabled quick healing of the fracture without the need to resort to a more proximal amputation. Conclusion: In these unusual cases, careful planning is necessary to ensure all aspects of the problem is dealt with. Each case should be treated on its own merits. Clinical relevance: This case demonstrates the difficulty in care of complex limb trauma and offers a solution for management of similar cases. Excellent results are possible when all surgical options are considered.